Effects of Nutrient Supplement and Chitosan on Microbial Population Change in Up-Flow-Anaerobic-Sludge-Blanket Reactor during Biogas Production - Piyaphanuwat, Rungroj; Samaimai, Srisuda; Limkhuansuwan, Vassanasak (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this research was to study the effects of nutrient supplement and chitosan on microbial change in an up-flow-anaerobic-sludge-blanket (UASB) reactor during biogas production. Three UASB reactors were operational in this study. All reactors were operated by feeding dilute stillage with chemical oxygen demand (COD) concentration at 10,000 mg/L and 9 days of hydraulic retention time (HRT) under anaerobic conditions. Reactor 2 and reactor 3 were supplemented with nutrient supplement and chitosan, respectively. The results of the environment and pH values of all UASB reactors showed similar conditions with total volatile acid/ alkalinity (TVA/Alk) values of 0.27-0.31. The COD removal efficiency of reactor 1 (stillage), 2 (stillage and nutrient supplement) and 3 (stillage and chitosan) showed about 79%, 84% and 87%, respectively. In addition, it was found that the UASB reactors supplemented with nutrient supplement or chitosan produced higher levels of biogas than those without additives. The 16S rRNA technique by PCR reaction showed that the dominant archaea in the final fermentation of all UASB reactors and in inoculum sample were hydrogenotrophic (genus Methanobacterium) and acetotrophic methanogens (genus Methanosaeta). The methanogens population in the reactor supplemented with chitosan (18.11%) produced more biogas than the ones in the reactor supplemented with nutrient supplement (14.44%) and in the control reactor (15.95%).